2013
DOI: 10.1136/bmj.f5847
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of financial incentives to improve adherence to maintenance treatment with antipsychotics: cluster randomised controlled trial

Abstract: Objective To test whether offering financial incentives to patients with psychotic disorders is effective in improving adherence to maintenance treatment with antipsychotics.Design Cluster randomised controlled trial.Setting Community mental health teams in secondary psychiatric care in the United Kingdom.Participants Patients with a diagnosis of schizophrenia, schizoaffective disorder, or bipolar disorder, who were prescribed long acting antipsychotic (depot) injections but had received 75% or less of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 36 publications
3
96
1
Order By: Relevance
“…Our findings suggest that this type of intervention could successfully be used to address adherence issues in BD patients, at least in those with high nonplanning impulsivity levels. Interestingly, a recent study (Priebe et al, 2013) reported on the effectiveness of financial incentives to improve adherence to maintenance treatment in bipolar patients. Finally, cognitive rehabilitation, which was found to display some efficacy to improve executive functioning in bipolar patients (Deckersbach et al, 2010), might enhance adherence in those with non-planning impulsivity.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings suggest that this type of intervention could successfully be used to address adherence issues in BD patients, at least in those with high nonplanning impulsivity levels. Interestingly, a recent study (Priebe et al, 2013) reported on the effectiveness of financial incentives to improve adherence to maintenance treatment in bipolar patients. Finally, cognitive rehabilitation, which was found to display some efficacy to improve executive functioning in bipolar patients (Deckersbach et al, 2010), might enhance adherence in those with non-planning impulsivity.…”
Section: Discussionmentioning
confidence: 97%
“…adherence ≤ 75%) l examine the views and experiences of both patients and clinicians with offering financial incentives to improve adherence to LAI medication to inform the concerns raised by focus groups 47,48 and Henderson and colleagues 49 and reproduced from Highton-Williamson and colleagues.…”
Section: Justification For the Current Studymentioning
confidence: 99%
“…Source: adapted from Priebe and colleagues. 47 This is an Open Access article distributed in accordance with the Creative Commons Attribution Non Commercial (CC BY-NC 3.0) licence,…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a linked paper (doi:10.1136/ bmj.f5847), Priebe and colleagues found that modest financial incentives significantly improved adherence in people treated with depot drugs for schizophrenia and other psychoses in the United Kingdom. 5 It is difficult to achieve adherence to antipsychotic drugs in people with psychoses for several reasons. Many do not accept that they are ill so do not believe that they need treatment.…”
mentioning
confidence: 99%